Health effects of laser printer emissions: a controlled exposure study. (2nd February 2017) - Karrasch, S.; Simon, M.; Herbig, B.; Langner, J.; Seeger, S.; Kronseder, A.; Peters, S.; Dietrich‐Gümperlein, G.; Schierl, R.; Nowak, D.; Jörres, R. A.
Abstract: Ultrafine particles emitted from laser printers are suspected to elicit adverse health effects. We performed 75‐minute exposures to emissions of laser printing devices (LPDs) in a standardized, randomized, cross‐over manner in 23 healthy subjects, 14 mild, stable asthmatics, and 15 persons reporting symptoms associated with LPD emissions. Low‐level exposures (LLE) ranged at the particle background (3000 cm −3 ) and high‐level exposures (HLE) at 100 000 cm −3 . Examinations before and after exposures included spirometry, body plethysmography, transfer factors for CO and NO (TLCO, TLNO), bronchial and alveolar NO, cytokines in serum and nasal secretions (IL‐1β, IL‐5, IL‐6, IL‐8, GM‐CSF, IFNγ, TNFα), serum ECP, and IgE. Across all participants, no statistically significant changes occurred for lung mechanics and NO. There was a decrease in volume‐related TLNO that was more pronounced in HLE, but the difference to LLE was not significant. ECP and IgE increased in the same way after exposures. Nasal IL‐6 showed a higher increase after LLE. There was no coherent pattern regarding the responses in the participant subgroups or single sets of variables. In conclusion, the experimental acute responses to short but very high‐level LPD exposures were small and did not indicate clinically relevant effects compared to low particle number concentrations.